Isolation of Streptococcus lactis bacteriophages and their interaction with the host cell - Parada, J.L. (1984)
Phages may cause lysis of lactic acid bacteria used in cheese production. Three virulent bacteriophages specific for Streptococcus lactis subsp. lactis C2 were isolated and purified from cheese whey. They showed distinct plaque sizes, and although they had similar morphology by electron microscopy examination, their dimensions were slightly different. The phage heads were elongated and hexagonal in shape, and the flexible tails appeared periodically cross-striated. They were DNA phages based on the acridine orange test. On infection, phage was adsorbed on the bacterial surface by the free end of the tail. After 80 min of incubation at 25°C, the phage heads appeared empty, slightly collapsed, and possessed a visible hollow tube through which the genetic material had been injected.